Assessing Effectiveness of Research for Load Shedding in Power System - Raghu C.N.; A. Manjunatha (Institute of Advanced Engineering and Science, 2017)
The research on loadshedding issues dates back to 1972 and till date many studies were introduced by the research community to address the issues. A closer review of existing techniques shows that still the effectiveness of loadshedding schemes are not yet benchmarked and majority of the existing system just considers the techniques to be quite symptomatic to either frequency or voltage. With an evolution of smart grids, majority of the controlling features of power system and networks are governed by a computational model. However, till date not enough evidences of potential computational model has been seen that claims to have better balance between the load shedding schemes and quality of power system performance. Hence, we review some significant literatures and highlights the research gap with the existing technqiues of load balancing that is meant for assisting the researcher to conclude after the selection process of existing system as a reference for future direction of study.